1982
DOI: 10.1111/j.1540-4560.1982.tb00115.x
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Political Perspective: Women and Drug Use

Abstract: Societies have usually regulated the use of drug substances with differences in rules of usage for men and women. This paper explores the political and historical factors contributing to this difference. Gender is linked to the use of drugs for therapeutic or recreational purposes and there seems to be greater social sanction for medicinal use for women. Women are bigger users of psychoactive drugs. Some possible reasons discussed are women's physiology, the relative health status of men and women, different a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1984
1984
2011
2011

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…For example, the proportion of the overall Australian It is also possible that community debate concerning cannabis and changes to its legal status in some Australian jurisdictions may be especially influential among women. Gomberg (1982) suggested that women might be more law-abiding than men, and that there was more stigma attached to women who use illegal street drugs. 24 The promotion of cannabis as a socially acceptable and harmless drug could be expected to reduce the stigma previously associated with cannabis use for females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the proportion of the overall Australian It is also possible that community debate concerning cannabis and changes to its legal status in some Australian jurisdictions may be especially influential among women. Gomberg (1982) suggested that women might be more law-abiding than men, and that there was more stigma attached to women who use illegal street drugs. 24 The promotion of cannabis as a socially acceptable and harmless drug could be expected to reduce the stigma previously associated with cannabis use for females.…”
Section: Discussionmentioning
confidence: 99%
“…Gomberg (1982) suggested that women might be more law-abiding than men, and that there was more stigma attached to women who use illegal street drugs. 24 The promotion of cannabis as a socially acceptable and harmless drug could be expected to reduce the stigma previously associated with cannabis use for females. Changes in rates of cannabis use among young females, and a lack of consistent gender differences were also reported in a recent German study of adolescent cannabis use, 25 suggesting that the pattern reported here may reflect a developing international trend.…”
Section: Discussionmentioning
confidence: 99%
“…22 Other authors have found that women's intoxication reduces social control of their sexuality, making them either more sexually disinhibited or more sexually vulnerable. 23 Traditionally, women's drinking has also been discouraged or concealed because it was incompatible with domestic roles, and might interfere with social control over family relationships and public behavior. 3,9,22 If gender differences in alcohol use have a sociocultural basis, as women's roles become similar to male roles, women and men's drinking behaviors would be expected to converge.…”
Section: Discussionmentioning
confidence: 99%
“…In some ways, however, feminist activism brought new attention to addiction, including alcoholism, among women (Gomberg, 1982;Filmore, 1984aFilmore, , 1984bFilmore, , 1986Herzberg, 2008). One measure of these changes was the establishment in the mid-1970s of an Office of Women's Programs in the NCA, the organization that had been founded by Marty Mann (Brown & Brown, 2001, pp.…”
Section: Psychiatry and Socialmentioning
confidence: 97%